Peningkatan Literasi Sains Melalui Pendekatan Brain-Based Learning: Penelitian Tindakan Kelas - Awalina, Fatikhatul Azmi; Utami, Nidya Chandra Muji; Rahmawati , Yuli (Cetta: Jurnal Ilmu Pendidikan, 2024)
The aim of this study is to improve the science literacy of elementary school students using a brain-based learning approach. The major problems found in this study include the inability of students to answer scientific questions relevant to real life, their inability to identify and interpret scientific texts, and their inabilidade to apply knowledge in everyday life. Brain-based learning methods were chosen because they were based on the principle of brain work. It is expected that this approach will help students become more interested and interested in studying Natural Sciences (IPA). Class Action Research (PTK), which consists of various action cycles, is used. Planning, implementation, observation, and reflection are phases that are included in each cycle. Data is collected through science literacy assessment using essays and observations. Content, context, high-level thinking, and affective aspects are the literacy components studied. The study involved 30 students who were in the fifth grade of primary school.  Students are better at identifying and interpreting scientific texts, answering scientific questions that are relevant to everyday life, and applying their knowledge to daily life. In addition, observations of student learning activity also show that students are more engaged and involved in the learning process. Students are more involved in discussions, questions, and experimental activities designed based on brain-based learning. In conclusion, the Brain- Based Learning approach is effective in improving students' science literacy.